Influence of Fastener Clip Loosening and Failure on Rail Head Lateral Displacement in Green Belt Embedded Tram Tracks - SHEN Jiqiang (Chengshi guidao jiaotong yanjiu, 2025)
[Objective] In green belt embedded tracks, the condition of fasteners cannot be directly observed, and measurements of rail geometry alone cannot intuitively reflect the fastener clips loosening or failure. As a result, timely and effective maintenance may not be implemented, leading to degradation of track alignment conditions. Therefore, it is necessary to study the influence of fastener clip loosening and failure on rail head lateral displacement in green belt embedded tram tracks. [Method] A rail overturning analysis model is established using finite element method. The rail is modeled with solid elements, while fastener clips, elastic baseplates, and lateral supports are modeled with nonlinear spring elements. The variation of clamping force is simulated by controlling the downward displacement of the spring, representing the clip pressure. The wheel-rail forces are divided into vertical and lateral components, applied as concentrated loads. The model is used to evaluate changes in rail head lateral displacement and contact length between the rail and elastic baseplate under various conditions, such as simultaneous failure of clips on both sides, failure on the inner side only, failure on the outer side only, and in the case of track gauge block detachment, under different amounts of clip loosening and varying numbers of failed clips. [Result & Conclusion] Under smaller wheel-rail lateral forces, the degree of clip loosening, the track gauge block detachment and the number of failed clips on both sides without detachment have minimal impact on rail head lateral displacement. When lateral forces increase, rail head lateral displacement will increase with greater clip loosening, though the trend remains gradual. Rail head lateral displacement also enhances as the number of failed dual-side clips increases. Under the same conditions, comparison between scenarios with and without track gauge block detachment shows similar rail overturning angles, but the lateral displacement of the rail base leads to an increased rail head displacement. When clips fail on the inner side, rail head displacement increases with more failed clips; the opposite effect is observed when clips fail on the outer side.